2020
DOI: 10.3171/2019.1.jns181598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of normal pressure hydrocephalus in 116 patients: objective versus subjective assessment

Abstract: OBJECTIVEObjective assessment tests are commonly used to predict the response to ventriculoperitoneal (VP) shunting in patients with normal pressure hydrocephalus (NPH). Whether subjective reports of improvement after a lumbar drain (LD) trial can predict response to VP shunting remains controversial. The goal in this study was to compare clinical characteristics, complication rates, and shunt outcomes of objective and subjective LD responders who underwent VP shunt placement.METHODSThis was a retrospective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In the elderly, aged ≥80 years, the estimated prevalence is ∼9% and, thus, far more frequent than in seniors < 80 years of age 3 . Early installation of a ventriculojugular or ventriculoperitoneal shunt has been reported to be an effective treatment 4–6 . However, the clinical appearance can vary among patients such that the typical triad is present in <60% of the patients 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, aged ≥80 years, the estimated prevalence is ∼9% and, thus, far more frequent than in seniors < 80 years of age 3 . Early installation of a ventriculojugular or ventriculoperitoneal shunt has been reported to be an effective treatment 4–6 . However, the clinical appearance can vary among patients such that the typical triad is present in <60% of the patients 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although shunt implantation (either ventriculoperitoneal or lumboperitoneal shunt) ameliorates the motor and cognitive (partly) disabilities of NPH, the extent to which surgery mitigates individual symptoms still varies widely among these patients. Currently, physicians rely mostly on the different clinical features (symptoms) of patients for iNPH diagnosis and prediction of treatment responsiveness [40]. Brain scans may help the diagnosis of this disease and are usually employed to detect secondary structural lesions, such as neurodegenerative diseases, stroke, or traumatic brain injury, which exhibit a similar and ambiguous disease presentation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to data collection, a research assistant who was a physiotherapist explained the details and demonstrated the timed up and go (TUG) test over the walkway. TUG is a widely used assessment tool to measure the effect of treatment on lower limb function and mobility [37][38][39] and proposed to use in diagnosis criteria 40 for iNPH. It demonstrated excellent reliability in elderly and chronic stroke.…”
Section: Data Collection Protocolmentioning
confidence: 99%